(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Metals are natural component of the ecosystem present throughout the layers of atmosphere; their abundant expression in the brain indicates their importance in the central nervous system (CNS). Within the brain tissue, their distribution is highly compartmentalized, the pattern of which is determined by their primary roles. Bio-imaging of the brain to reveal spatial distribution of metals within specific regions has provided a unique understanding of brain biochemistry and architecture, linking both the structures and the functions through several metal mediated activities. Bioavailability of essential trace metal is needed for normal brain function. However, disrupted metal homeostasis can influence several biochemical pathways in different fields of metabolism and cause characteristic neurological disorders with a typical disease process usually linked with aberrant metal accumulations. In this review we give a brief overview of roles of key essential metals (Iron, Copper and Zinc) including their molecular mechanisms and bio-distribution in the brain as well as their possible involvement in the pathogenesis of related neurodegenerative diseases. In addition, we also reviewed recent applications of Laser Ablation Inductively Couple Plasma Mass Spectrophotometry (LA-ICP-MS) in the detection of both toxic and essential metal dyshomeostasis in neuroscience research and other related brain diseases